The Legal Study of Materiil Testing Rights Supreme Court in Indonesia - Ni Luh Gede Astariyani (Universitas Bali Dwipa, 2022)
The authority of the Supreme Court to examine statutory regulations under the law or in this case referred to as judicial review is a mandate of the 1945 Constitution. Article 24A paragraph (1) of the 1945 Constitution which is the result of the Third Amendment states,